PENGARUH SIMPLISIA DAUN PEPAYA TERHADAP KECUKUPAN ASI PADA BAYI USIA 0-6 BULAN DI DESA PURBA TUA KECAMATAN PADANGSIDIMPUAN TENGGARA TAHUN 2021 - Harahap, Maryam Latifah; Siregar, Rahmah Juliani (Jurnal Ilmiah Keperawatan, 2022)
Breast milk contains high nutrients and substances that are useful for the needs of optimal growth and development needed by babies. Its high nutritional content and the presence of immune substances in it make breast milk the main and most perfect source of food for babies. Breast milk contains substances for development, intelligence, immune substances (prevents various diseases), can establish love between mother and baby, delay pregnancy, reduce the risk of breast cancer, and is a special happiness for mothers (Linda, 2019). One of the factors that causes a lack of breastfeeding is less milk production. Problems in the mother are inverted nipples, mastitis or breast abscess, swollen breasts, and sore nipples. In infants, generally it is an error in lactation management, which causes a decrease in breast milk production (lack of breast milk syndrome) (Kumala, Rini, 2017). Papaya leaf simplicia contains alkaloids that are useful for breastfeeding mothers in facilitating breast milk. Because the content can stimulate the release of breast milk (Kurnia, 2018). The purpose of this study was to find out how the Effect of Papaya Leaf Simplicia (Carica Papaya L) on the Adequacy of Breastfeeding in Infants Age 0-6 Months in PurbaTua Village, Southeast Padangsidimpuan District in 2021. Types The research used was experimental research with a prettestposttest only control group design. Using purposive sampling with the number of respondents as many as 16 people, namely the experimental group respondents as many as 8 people and the control group as many as 8 people. Based on the results of the study, it showed that there was an effect of papaya leaf simplicia (Carica Papaya L.) on the adequacy of breast milk in infants aged 0-6 months in PurbaTua Village, Southeast Padangsidimpuan District in 2021 with p-value = 0.028 <0.05. This study is expected to be useful for midwifery services and the development of midwifery science in using papaya leaf extract as an alternative to facilitate breastfeeding so that breastfeeding is sufficient. It is recommended for postpartum mothers, in order to get sufficient milk output, they can use alternatives to consume papaya leaf simplicia (Carica Papaya L) during breastfeeding.